2020
DOI: 10.21203/rs.3.rs-27902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of facet-joint degeneration on the in vivo motion of the lower lumbar spine

Abstract: Objective This research studied the in vivo motion characteristics of the L3-S1 lumbar spine with facet-joint degeneration during functional activities. Methods Thirteen male and 21 female patients with facet-joint degeneration at the L3-S1 spinal region were included in the study. The L3-S1 lumbar segments of all the patients were divide into 3 groups according to the degree of facet joints degeneration (mild, moderate or severe). The ranges of motion (ROM) of the vertebrae was analyzed using a combination … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Some studies have suggested tropism of lumbar facet joints, as a contributing factor in the development of LDH [5,9,14,15]. Wang et al [7] measured 65 LDH patients by MRI and compared them with 30 normal subjects and found that FT was present in 20 LDH patients compared with 3 controls, and the difference was statistically signi cant; Chadha et al [11]studied 60 LDH patients and found that 25 had disc herniation at L4/5, 35 at L5/S1, 6 at L4/5 in the observation group, 3 in the control group (P = 0.145), 13 at L5/S1 in the observation group, and 1 in the control group (P = 0.0094) by MRI; Some studies have held the opposite opinion that there is no association between facet joint tropism and LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested tropism of lumbar facet joints, as a contributing factor in the development of LDH [5,9,14,15]. Wang et al [7] measured 65 LDH patients by MRI and compared them with 30 normal subjects and found that FT was present in 20 LDH patients compared with 3 controls, and the difference was statistically signi cant; Chadha et al [11]studied 60 LDH patients and found that 25 had disc herniation at L4/5, 35 at L5/S1, 6 at L4/5 in the observation group, 3 in the control group (P = 0.145), 13 at L5/S1 in the observation group, and 1 in the control group (P = 0.0094) by MRI; Some studies have held the opposite opinion that there is no association between facet joint tropism and LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are no longer limited to in vivo research, more researchers are gradually moving to in vitro research [6,14,19,25]. And many reasons are considered, such as the movement pattern, the degeneration level of the facet joint [31] or the weight-bearing condition [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, if microarthritis occurs, the joint load with abnormal joint force can reach up to 47% [30], The probability of low back pain has also greatly increased. Yin et al [31] analyzed the effects of three groups of facet joints with different degrees of degeneration on the movement of the lumbar vertebrae through computed tomography combined with dual-perspective imaging technology, and found that the degeneration of facet joints would change the ROM of the lumbar spine. And as the degree of facet joint degeneration increases, the initial increase in lumbar spine ROM decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation